Achieving Stable Throughput to Support QoS in IEEE 802.11 Wireless Networks - Md Khambari, M. N.; Sahib, S.; Othman, M. F. I. (2009)
This paper investigates and describes a new provisioning technique for IEEE 802.11 based networks, focusing on the ad-hoc Distributed Coordination Function (DCF) to redefine stability of the network throughput to support QoS. This paper propose better techniques to achieve stable throughput in Wireless LAN networks by assigning new values to the Contention Window to high priority traffics which will guarantee better throughput to the selected network traffic. A simulation is done using Network Simulator 2 (NS-2) and findings are then presented. Results showed that stable throughput can be achieved to provide better traffic flows especially for real-time traffic and multimedia applications.